Growth of Bacillus toyonensis in Tofu Wastewater. Issue 1 (November 2021) - Nursyirwani, N; Yoswaty, D; Oktavia, D A
Abstract: Bacillus toyonensis has been isolated in Dumai mangrove ecosystem of Riau Province. One of factors affecting the growth of the bacteria is growth substrate. Tofu wastewater is rich in nutrition which can be used as substrate for bacterial growth. This research aimed to observe the growth of B. toyonensis in different concentration of tofu wastewater. The bacteria was grown in tofu wastewater at concentrations 8%, 10% and 12% was supplemented with 0.1 g K2 HPO4, 0.15 g KH2 PO4, 0.15 g NaCl and 0.5 g vitamin B12 in 100 mL distilled water. The bacterial growth was observed by using spectrophotometer at λ 610 nm and by analysis the total plate counts on plate count agar (PCA) at 0, 24, 48, 72 and 96 hour cultivation. Spectrophotometric observation showed that the highest bacterial growth of all tofu wastewater treatments indicated by the addition of 12% tofu wastewater, although the absorbance value was lower than culture in tryptic soy broth (TSB) as control. Exponential growth occurred between 0-24 hour incubation, and the highest growth indicated in substrate contained 12% tofu wastewater. Similarly, total plate count (TPC) analysis indicated that the highest bacterial growth of all treatment occurred at 24 hours incubation, and the highest count was also indicated by treatment of 12% tofu wastewater (2.42±0.06×10 8 CFU/mL). In conclusion, tofu wastewater can be an alternative substrate for the bacterial growth.